2006
DOI: 10.4103/0972-5229.27858
|View full text |Cite
|
Sign up to set email alerts
|

Laryngeal sequelae following prolonged intubation: A prospective study

Abstract: Background: Laryngeal injuries following intubation have a reported incidence from 63 to 94% and permanent sequelae are reported to be about 10 to 22% in the world literature. While several studies assessing the laryngeal complications are available in Caucasoid populations, minimal data is available in the literature regarding south Indian population. Aim: The aim of this study was to evaluate laryngeal lesions in patients after prolonged intubation (>24 h), to correlate these lesions with the variables invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 9 publications
(7 reference statements)
0
24
0
2
Order By: Relevance
“…26 There was an alarming increase in the incidence of LTS especially in children following endotracheal intubation which Othersen called it "a new epidemic." 27 The reported incidence of laryngotracheal injuries following endotracheal intubation varied from 62 8 to 94% for temporary laryngeal injuries 28 and 10 to 20% of these result in permanent laryngeal sequelae such as LTS. The incidence of laryngotracheal injuries reportedly had reduced after the use of "high-volume low-pressure cuffed endotracheal tubes."…”
Section: Discussionmentioning
confidence: 99%
“…26 There was an alarming increase in the incidence of LTS especially in children following endotracheal intubation which Othersen called it "a new epidemic." 27 The reported incidence of laryngotracheal injuries following endotracheal intubation varied from 62 8 to 94% for temporary laryngeal injuries 28 and 10 to 20% of these result in permanent laryngeal sequelae such as LTS. The incidence of laryngotracheal injuries reportedly had reduced after the use of "high-volume low-pressure cuffed endotracheal tubes."…”
Section: Discussionmentioning
confidence: 99%
“…Mann-Whitney U test or independent sample t test was used between two groups, and analysis of variance was used to assess the significance of differences among 3 groups as appropriate. We enrolled patients scheduled for cardiac surgery due to the lengthy intubation involved during surgery and during monitoring in intensive care [10][11][12]. We observed correlation between total length of intubation and effects in laryngopharyngeal structures.…”
Section: Discussionmentioning
confidence: 99%
“…Various postoperative complications are seen in patients undergoing cardiac surgery, particularly vocal cord paralysis associated with recurrent laryngeal and vagal nerve trauma, and these complications may result in prolongation of intubation and of stay in intensive care [9][10][11][12]. We determined vocal cord paralysis in one case, but the patient was referred for clinical follow-up since the respiratory functions were not affected.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that temporary LTI occurred in 62-94% of intubations [8]. A number of factor influence the severity of injury and the progress to formation of SGS.…”
Section: Discussionmentioning
confidence: 99%